The Brain Drain of the Egyptian Physicians: A Look from Both Sides - Ismail, Hebatalla Ahmed Mohamed (AUC Knowledge Fountain, 2024)
The brain drain of well-educated and trained workers is a problem that faces many nations. The pandemic revealed the importance of being ready with all resources, especially the healthcare workers. In Egypt, according to records of the Egyptian medical syndicate, half of the registered physicians in the syndicate are working abroad. In this study, we aimed to understand the relationship between individual satisfaction regarding work or family, his capability factors, and his intention to leave the country to work in another one. A quantitative approach was used by a self-administered online questionnaire. The results showed that 66.4% of physicians who are working in Egypt had the intention to leave. The factor that had the highest impact on their decision was work satisfaction, where the less satisfied physicians were 20 times more likely to leave. Besides, the participants with lower economic status were more willing to leave. Also, other factors that can be associated are gender, age, and being financially responsible. On the other hand, only 6.8% of Egyptian physicians who are living abroad were considering going back home and working there. The only factor that showed an association with their intention was their age, as more of the older participants had this intention. It is concluded that the high level of dissatisfaction among physicians with their work environment will lead to significant resource losses for other countries. Factors should be addressed, and intervention strategies are urgently needed for physicians retention to achieve Egypt’s Vision 2030 for health and economic growth.